Meningkatkan Antarmuka Pengguna Melalui Analisis Sentimen: Mengungkap Pengalaman Pengguna di Aplikasi Bukalapak - Ikhwan Arief; Muhammad Farhandika; Ahmad Syafruddin Indrapriyatna; Ardhian Agung Yulianto; Yumi Meuthia (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2023)
In this research, we use sentiment analysis to refine the user interface (UI) and user experience (UX) of the Bukalapak application, a leading online trading platform in Indonesia. We focus our scrutiny on 4,462 reviews related to the UI within a larger dataset of 246,947. Almost a third of these critiques express dissatisfaction, predominantly pointing out issues related to the UI design and its functionality. The critiques underscore the potential of sentiment analysis as a tool to uncover areas of user-centric design that need improvement. To address these issues, it is necessary to incorporate user feedback and sentiment analysis into the design workflow, allowing a more in-depth understanding of user needs and facilitating more effective service enhancements. Embracing a user-centered methodology allows for UI fine-tuning, leading to better functionality and increased user contentment. Our investigation reveals a positive link between design refinements and usability ratings, indicating improved user experience satisfaction. To summarize, this research highlights the essential contribution of user feedback and sentiment analysis to detect and correct UI shortfalls, thus augmenting UX and contributing to the triumph of platforms like Bukalapak within Indonesia's dynamically changing e-commerce environment.